Individual 3D-Printed Implants Made from a Copolymer of Vinylidene Fluoride with Tetrafluoroethylene: Studies of the Effects of Steam Sterilization on Structure and Toxicity; Biomedical Engineering; Vol. 57, iss. 1 - Vorobjev A. O. Aleksandr Olegovich; Kulbakin D. E. Denis Evgenjevich; Chistyakov S. G. Sergey Gennadevich; Mitrichenko A. D. Aleksey Dmitrievich; Dubinenko G. E. Gleb Evgenjevich; Akimchenko I. O. Igor Olegovich; Plotnikov E. V. Evgeny Vladimirovich; Gogolev A. S. Aleksey Sergeevich; Choynzonov E. L. Evgeny Lkhamatsyrenovich; Buznik V. M. Vyacheslav Mikhaylovich; Bolbasov E. N. Evgeny Nikolaevich (2023, 2023)
Title screen